Error Analysis On The Use of Simple Past Tense Among The Second Year Students Of SMP Inshafuddin Banda Aceh - Endah Anisa Rahma; Muhammad Gustian Safrilla; Jusnaini Hasni; Ana Elvia Jakfar; Refanja Rahmatillah (INNOVATION RESEARCH JOURNAL, 2024)
Tense is a part of grammar unit that must be mastered by L2 learners. For some L2 learners, the simple past tense is considered as a challenging tense to learn. This issue can be seen on the test given to the students at SMP Inshafuddin Banda Aceh. Hence, this study aimed to find out the common errors produced by second-year students and errors described on the frequency occurrence of the errors made among students on the use of simple present at SMP Inshafuddin Banda Aceh. The study used descriptive qualitative and descriptive quantitative research methods and employed purposive sampling technique to collect the data. There were 45 second-year students of SMP Inshafuddin Banda Aceh participated in the study. The data was collected by giving a writing test to the students. There were two types of the test; identification and identification of errors. Next, the data collected was analyzed by forming a reconstruction of sentence correction in the target language; identifying the errors, and classifying the errors. The findings of the study presented that the most common error made by students on the use of simple past tense is misformation. Meanwhile, the frequency of errors on the use of simple past tense shows that the most common error types are on the error of misformation. Two types of errors identified as the most difficult items are errors of addition and errors of misformation where these types were categorized as “fair”. Meanwhile, errors of omission and errors of misordering were categorized as “good”.